Agro-morphological characterisation and selection of sorghum landraces. (3rd October 2018) - Derese, Solomon Assefa; Shimelis, Hussein; Mwadzingeni, Learnmore; Laing, Mark
ABSTRACT: Sorghum [ Sorghum bicolor (L.) Moench] grown under rain-fed conditions is frequently affected by drought stress at different stages, resulting in reduced grain and biomass yield. The aim of this study was to characterise sorghum landraces and to select farmer-preferred medium-maturing genotypes under rainfed and irrigated conditions. Hundred and ninety-six sorghum accessions were evaluated at Kobo site of the Sirinka Agricultural Research Center in 2014/2015 in Ethiopia. Data collected from 14 traits were subjected to analysis of variance, cluster analysis, Pearson's correlation coefficient analysis, path coefficient analysis and principal component analysis (PCA). Significant genotypic differences ( p  < 0.05) were observed. Medium-maturing and drought tolerant sorghum genotypes including E-72457, E-72438, E-72435, E-206214, E-72449, E-75460 and E-75458 with superior agronomic performance were recommend for large-scale production or for further breeding. The genotypes evaluated under rain-fed and irrigated conditions were grouped into five and six clusters, respectively, representing varied different heterotic groups. Grain yield had significant and positive correlation with yield-related traits assessed under the two test conditions. Further, path coefficient analysis revealed that days to maturity under rainfed condition and harvest index under irrigated condition had the highest positive direct effects on grain yield, therefore can be targets for direct selection. Overall, there was marked genetic diversity among the tested genotypes. Suitable medium-maturing farmers-preferred accessions selected from the study will be useful for effective breeding for drought tolerance and medium-maturity.